2008
DOI: 10.1007/s12031-008-9132-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of PACAP on Oxidative Stress and Tissue Injury Following Small-Bowel Autotransplantation

Abstract: Tissue injury caused by cold preservation and reperfusion remains an unsolved problem during small-bowel transplantation. Pituitary adenylate cyclase-activating polypeptide (PACAP) is present and plays a central role in the intestinal physiology. This study investigated effect of PACAP-38 on the oxidative stress and tissue damage in autotransplanted intestine. Sham-operated, ischemia/reperfusion, and autotransplanted groups were established in Wistar rats. In ischemia/reperfusion groups, 1 h (group A), 2 h (gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…PACAP injection. The results are in accordance with the findings of earlier studies, where the changes of SOD activity were measured in intestinal ischemia/reperfusion [8]. the protective effect of pacap has also been shown in oxidative stress-induced kidney injury in vitro [17].…”
Section: Effect Of Exogenous Pacap In Ischemia/reperfusion-induced Kisupporting
confidence: 92%
See 1 more Smart Citation
“…PACAP injection. The results are in accordance with the findings of earlier studies, where the changes of SOD activity were measured in intestinal ischemia/reperfusion [8]. the protective effect of pacap has also been shown in oxidative stress-induced kidney injury in vitro [17].…”
Section: Effect Of Exogenous Pacap In Ischemia/reperfusion-induced Kisupporting
confidence: 92%
“…This protective effect was first described in global and focal cerebral ischemia [32,42,48]. Subsequently, the protective effects of PACAP were reported in ischemic injury of the retina [4] and in ischemia/reperfusion-induced damages of peripheral organs, such as in intestinal, cardiac and liver ischemia/reperfusion [8,20,39].…”
Section: Effect Of Exogenous Pacap In Ischemia/reperfusion-induced Kimentioning
confidence: 94%
“…The present observations are in accordance with our previous observations, where we have shown that adding exogenous PACAP-38 to UW solution prevented the elevation of lipid peroxidation and the reduction in endogenous scavenger capacity in rat small intestine. The intestinal structure was also significantly better preserved in small bowel autotransplantation model when PACAP-38 was added to the preservation solution (Ferencz et al 2009b). These observations support the role of PACAP-38 in tissue preservation in cold preservation model of transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…These include primary graft non-or dysfunction, endotoxemia, peritonitis, and risk of acute/chronic rejection. Given the negative effect of this phenomenon, efforts are being made to recognize, modulate, minimize, or even eliminate it (Carden and Granger 2000;Ferencz et al 2009b;Balaz et al 2004;Mallick et al 2004Mallick et al , 2005.…”
Section: Discussionmentioning
confidence: 99%
“…PACAP has been shown to have protective effects against ischemia-induced tissue damage in the nervous system and also in the periphery, such as in the small intestine (Ferencz et al 2009;Ohtaki et al 2008). Ischemia/ reperfusion injury is characterized by common mechanisms in all tissues.…”
Section: Introductionmentioning
confidence: 99%